Pelatihan Pembuatan Bedcover Kaca (Kain Perca) Untuk Bekal Wirausaha di Panti Asuhan Bina Insani Ngawi - Ratih Kusuma Dewi; Afi’ah Citra Nur Mualifah; Alvian Viki Praditiya (Jurnal Pengabdian Pada Masyarakat, 2017)
The aim of Bedcover Training is to train skill and capability in enterpreunership of orphanage students as skill capital to create business chance and independent business field. The training was held in Bina Insani Orphanage in Ngawi on May 25th -26th, 2017. The members are 40 students and divided into 8 small groups. The training produces 5 sheets of bedcover. The training of making bedcover is intended for arousing innovative thinking of Ngawi Bina Insani Orphanage students. The making bedcover is aimed to economize raw material by utilizing some wasted materials.